The Effect of Self Compassion on Fear of Childbirth in Primigravida - Erika Putri Prasetya; Finta Isti Kundarti; Wiwin Martiningsih (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2026)
Fear of childbirth (FOC) is a widespread concern experienced by many pregnant, it was reported that 54.8% of first-time pregnant low FOC, and 45.2% very high fear. Self-compassion can help prevent or reduce fear during childbirth. This study aimed to determine the effect of a self-compassion intervention on the level of FOC in pregnant. This study used a quasi-experimental pretest–posttest design with a control group, involving a total sample of 60 first-time pregnant divided into an experimental group (n = 30) and a control group (n = 30) using a simple random sampling technique. This study was conducted in the Sukorejo Community Health Center in April until May 2025. T-test showed a significant decrease in the FOC level in the experimental group from m = 56.10 (SD = 20.436) to m = 31.80 (SD = 18.773) with a p value = 0.000. The control group from m = 56.17 (SD = 23.976) to m = 56.90 (SD = 22.715) with a p value = 0.481. Self-compassion is effective in reducing fear of childbirth. Self-compassion interventions can be a complementary therapy to conventional therapy that is easy for pregnant women to do.